Morphological characterization of indigenous goats in selected districts of West Shewa Zone, Oromia regional State, Ethiopia - Kassahun Bekana Kitila; Abera Teshome Aleli; Solomon Shiferaw Tufa (PLoS ONE, 2025)
This study was conducted in the West Shewa Zone to identify the morphological characteristics of the indigenous goat population. Data were collected from 519 goats, including body measurements and observations. Qualitative data were analyzed descriptively, while quantitative data were analyzed using the GLM procedure. The average flock size per household was 11.30 ± 7.17, with the Ejere district having the largest flocks compared to other districts. Significant differences were observed in most qualitative traits among the goat populations across the four districts. These traits included horn presence, beard presence, coat color pattern, coat hair type, horn shape, head profile, horn orientation, and ear orientation. The majority of goats displayed a patchy coat color, smooth and short hair, straight horn shape, backward horn orientation, straight head profile, and horizontal ear orientation. The overall means for body weight, body length, heart girth, wither height, pelvic height, rump length, rump width, horn length, and ear length were 29.03 ± 3.91 kg, 65.09 ± 3.60 cm, 70.87 ± 3.84 cm, 65.97 ± 3.75 cm, 68.23 ± 3.35 cm, 19.27 ± 2.11 cm, 13.75 ± 1.65 cm, 10.89 ± 2.77, and 14.00 ± 1.37 cm, respectively. Significant differences (p < 0.05) in most body measurements were observed based on sex, and age. In the interaction, some of them were found to be significant differences, while only a few measurements showed differences between districts. Body weight and heart girth exhibited a stronger correlation than other linear body measurements. For female goats, heart girth, body length, and pelvic height significantly influenced body weight predictions, whereas for male goats, only heart girth was a relevant measurement. In conclusion, the observed variations in most morphological traits indicate the necessity of developing selective breeding strategies to enhance economically significant traits in goat farming.